Clinical encounters of Australian general practice registrars with paediatric patients. Issue 2 (4th March 2017) - Hiscock, Harriet; Freed, Gary; Morgan, Simon; Tapley, Amanda; Holliday, Elizabeth; Davey, Andrew; Ball, Jean; van Driel, Mieke; Spike, Neil; McArthur, Lawrie; Magin, Parker
Abstract: Background : Whether general practitioner (GP) registrars have adequate exposure to, and feel confident in, managing children's health during training is unknown.Objectives : To determine the prevalence and associations of GP registrars' paediatric vs. non-paediatric consultations.Methods : Cross-sectional analysis from a cohort study of Australian GP registrars' 2010–2014 consultations.Results : 889 registrars contributed details for 26, 427 (21.8% (95% CI: 21.4–22.2) paediatric consultations. Paediatric patients were more likely to be male and new to the practice. Although paediatric patients were less likely to have a chronic disease (OR 0.38, 95% CI 0.36, 0.40) and presented with fewer problems (OR 0.59, 95% CI 0.57, 0.61), registrars were more likely to seek in-consultation advice (OR 1.25, 95% CI 1.19, 1.31) and generate learning goals (OR 1.12, 95% CI 1.07, 1.18) for paediatric consultations.Discussion : GP registrars appear to feel less confident in managing paediatric compared with adult consultations, suggesting an unmet training need.